(untitled) (Zdravstveni glasnik, 2024)
Introduction: The most important biochemical reactions of the human organism take place in the liver, and therefore it represents one of the most important organs for life. Parameters that play an important role in the diagnosis and monitoring of patients are the enzymes ALT, AST, GGT, ALP, and bilirubin. Objective: To evaluate the serum activity of enzymes and bilirubin in patients with liver cirrhosis and liver cancer. Materials and methods: The study included 120 patients aged over 50 years. Among them, 40 patients had liver cirrhosis, 40 had cancer and liver metastases, and 40 patients were apparently healthy (control group). The concentrations of AST, ALT, GGT, and ALP were determined on Abbott Architect i2000sr biochemical analyzer and Dimension analyzer. Results: The study showed that the mean values of the studied parameters were significantly higher in subjects with liver cirrhosis and cancer with liver metastases than in the control group. A statistically significant difference (p <0.05) was found in ALP and bilirubin concentrations between the studied groups. In addition, the study revealed a statistically significant difference (p <0.05) in ALT, AST, and GGT activity between subjects with cancer and the control group and subjects with cirrhosis and the control group. Conclusions: The results confirm that the activities of enzymes ALT, AST, GGT, ALP, and bilirubin were increased in subjects with cirrhosis and cancer compared to the control group.